Mononuclear phagocytes and HIV infection - Poli, Guido (Henry Stewart Talks, 2012)
The HIV pandemic, HIV structure, HIV target cells and their viral receptors, HIV life cycle, Macrophages as "Trojan horses" of HIV, Comparison of HIV infection of T cells and macrophages, Macrophage differentiation, HIV infection of bone marrow precursors in vitro and in vivo, Functional defects of monocytes, HIV and tissue macrophages, HIV and the brain, HIV and intestinal macrophages, HIV replication in monocytic cell lines, U937 and U1 cell lines, HMGB1 and HIV infection of U937 cells, U937 cell clones and TRIM22, IFNs and HIV infection of macrophages, Human macrophage polarization and HIV infection, Macrophage polarization and inhibition of HIV replication, Differences between M1 and M2 macrophages in inhibiting HIV replication